Hipoteza Sapira-Whorfa – przegląd argumentów zwolenników i przeciwników - Klimczuk, Andrzej (Kultura-Społeczeństwo-Edukacja, 2013)
Nowadays is growing importance of interdisciplinary research and in the field of cultural diversity, multiculturalism and intercultural cooperation. It is important also to take into account the global processes of changes associated with the dissemination of digital information and communication technologies. One of the theories which are essential in this area of research is the concept by E. Sapir and B.L. Whorf. The purpose of the article is to introduce into a current condition of scientific dispute concerning the views of these authors on the relationship between language and cognition. Paper is based on a critical analysis of the literature. In conclusion, the main findings and recommendations for further research were identified.